Hubungan Intensitas Pengamalan Zikir Al-Awräd Dengan Kedisiplinan Santri Di Pondok Pesantren Putri Ar- Roudloh Ngronggo Kota Kediri - Al-Chusna, Firsa Asa Imamal (Spiritualita, 2018)
Recently, research on the intensity of the practice of dzikir became an interesting study as a method to improve the discipline of santri. In the Islamic boarding school, discipline is one of the most important things in order to achieve optimal results in accordance with the vision and mission of Pesantren. Because the better the discipline of santri, the higher the santri’s achievements are reached. The purpose of this research was to find out the correlation between the intensity of dzikir Al-awrad, as the routine’s dzikir of Pesantren ar-Roudloh located in Ngronggo, Kediri, with the discipline of santri. The research is used quantitative method by Pearson Product Momen correlation analysis. The data collection was obtained from questionnaires with total sample of 83 people. The results showed that the level of intensity of dzikir Al-awrad was included in the medium category with a score of 59-92 or 74.70%. While the level of discipline was in high category with the range scores of 38-51 or 67.47%. Between the intensity of dzikir practice and the discipline variable are correlated with a significance value of 0,000 (0,000 <0,05) or Ha is accepted. So it can be concluded that there is a positive correlation between the intensity of dzikir Al-awrad practice and the discipline of santri in the Islamic Boarding School of ar-Roudloh, Kediri City.